Various presentations, diagnosis, and management of enteric duplication cysts in high-volume tertiary healthcare center - Atul Kumar Khare,; Geetesh Ratre,; Ashok Kumar Chopra,; Pankaj Goyal,; Ashish Paliwal,; Aditya J Baindur,; Kirti Singh,; Vinayakumar Shelke, (Asian Journal of Medical Sciences, 2025)
Enteric duplication cysts (EDCs), while having an incidence of 1 in 4500 live births, are not often diagnosed antenatally. Patients who are eventually diagnosed to have EDC have a varying presentation, demographically and clinically. EDCs are classified as cystic and tubular, with the latter being radiologically difficult to detect on ultrasound as compared to the cystic variant, and therefore requiring further investigations. With other differential diagnoses of mesenteric cysts and omental cysts, the clinical incidence of EDC is also reduced. This study was done over a 2-year period, where patients who were diagnosed with EDC at Sir Padampat Institute of Neonatology and Child Institute, Jaipur, were included in the study. They were monitored from the time of diagnosis, assessing their demographic data, pre-operative status, surgical management, post-operative treatment, and follow-up after discharge. A total of 14 patients were included in the study, of which a majority were tubular variants of ileal duplication cyst. Three patients had foregut duplication cysts (1 gastric and 2 esophageal). The age ranged from 3 days to 10 years, with the average age of 2.2 years. Each child had a varying presentation, some of them presenting with complications such as obstruction and perforation. The incidence was more in male children, as compared to females (3.6:1 – male: female). Two children had associated anomalies (one had a congenital diaphragmatic hernia and one had malrotation of the gut). In one child, a foregut duplication cyst was found to be communicating with a dilated segment of the jejunum, which was resected together. EDCs, while rare in occurrence, can have a myriad of presentations, and other associated congenital anomalies. Further studies are required to identify attributing risk factors and regional incidence along with better awareness for antenatal screening of EDCs.